(3GdhbGjI hGdYdGL ef CeQGV GdSQWGfs - (3eUWai, eMeOs; (3GdfLGQ, YHO GdQMefs; (3GdfLGQ, YHO GdfGUQs ((3GdbGgQIs (3OGQ GdCeds, 2007)
(3eQV GdYUQ GdPj GHJdjJ Hg GdHTQjI dJOaY Kef gQhdJgG fMh GdJbfjI GdMOjKI h GdJWhQ dJZjQ ef GdWHjYI Ohf Cf JOQc GdYhGbH, acGf gPG GdhHGA GdaJGc GdPj jgLe HTQGSI, Efg jCJj Ohf ehYO Ch SGHb EfPGQ djaJc HGdHTQs
(3GdeMJhjGJ (B: (3GdSQWGf Ydi eQ GdYUhQ (B- - (3GfJTGQ GdChQGe (B- - (3JYQja GdSQWGf (B- - (3CfhGY GdSQWGf GdeNJdaI (B- - (3SQWGf GdSjL GdHTQj (B- - (3BdjI eQV GdSQWGf (B- - (3cja jHOC GdSQWGf (B- - (3ecGaMI eQV GdSQWGf (B- - (3GdhbGjI ef GdSQWGf (B- - (3GdYhGed GdeSHHI ddSQWGf (B- - (3GdaMU GdeHcQ fbWI OaGY VO GdSQWGfs
1 9 21
Keywords: (3GdChQGes; (3GdSQWGfs -- (3eQVs; (3GdSQWGfs -- (3hbGjIs